2013
DOI: 10.1074/jbc.m112.436022
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric-oxide Synthase Activation Generates an Inducible Nitric-oxide Synthase-like Output of Nitric Oxide in Inflamed Endothelium

Abstract: Background:In healthy endothelium, agonist-induced eNOS activation results in transient, calcium-dependent NO production. Results: In inflamed endothelium, bradykinin stimulates prolonged eNOS-derived NO that depends on G␣ i , MEK1/2, and JNK, resulting in reduced migration. Conclusion: eNOS activation is mediated differently in normal and inflamed endothelium, resulting in divergent NO production and effects. Significance: High eNOS-derived NO may impair angiogenesis and wound healing in inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 90 publications
0
38
0
Order By: Relevance
“…Therefore, we investigated the possibility that ERK and JNK activation also contribute to LPS-induced STIM1 expression in HLMVECs. Here we used a pharmacological approach to prevent the activation of ERK and JNK in HLMVECs (42). We observed that the ERK inhibitor PD98059 prevented LPS-induced ERK phosphorylation (Fig.…”
Section: Lps Priming In Vivo Potentiates Par-1-induced Increase In Lumentioning
confidence: 99%
“…Therefore, we investigated the possibility that ERK and JNK activation also contribute to LPS-induced STIM1 expression in HLMVECs. Here we used a pharmacological approach to prevent the activation of ERK and JNK in HLMVECs (42). We observed that the ERK inhibitor PD98059 prevented LPS-induced ERK phosphorylation (Fig.…”
Section: Lps Priming In Vivo Potentiates Par-1-induced Increase In Lumentioning
confidence: 99%
“…As a result of experiments conducted in the presence of frovatriptan (5×10 -5 mol/l), the contractile response to L-norepinephrine was signifi cantly increased compared to control reaction on the carotid artery. Our results also suggest that frovatriptan predominantly at higher concentrations probably by non-specifi c mechanism, which could activate the following intracellular chain reaction: stimulation on α 1D → activation of eNOS → increase in the concentration of NO 16 and subsequent relaxation, which is atypical for the triptans.…”
Section: Effects Of 5×10 -5 Mol/l Frovatriptan On the Con-tractile Acmentioning
confidence: 76%
“…NO causes a decrease in platelet cytosolic Ca 2+ , which influences platelet glycoprotein activation, and therefore, platelet adhesion (63). NO can also inhibit fibrin deposition, further attenuating thrombus formation (137). In contrast, EC-generated ROS acts to promote platelet activation and aggregation (42 Figure 3 The role of the pulmonary endothelium in platelet function.…”
Section: Coagulationmentioning
confidence: 98%